Surfacing factors that prevent small businesses in economically deprived areas from growing: a multiple case study in Site C, Khayelitsha - Ncoliwe, Lwazi (Graduate School of Business (GSB), 2019)
The research identified Site C area of Khayelitsha, a township in the Western Cape Province of South Africa, as the case study. Khayelitsha is a historically black township situated on the periphery of Cape Town. Site C is an area which was built around one of the old formal areas, and is made up of different types of dwellings: it contains a large number of informal settlements, Reconstruction and Development Programme (RDP) houses, and informal, backyard dwellings. The prime objective of the study was to surface factors that prevent black-owned small, medium and micro enterprises (SMMEs) in the socio economically deprived area of Site C, Khayelitsha, from growing despite the support provided by government. The secondary objective was to determine what role government could play to effectively assist and promote such SMMEs, and to explore possible interventions to address the common challenges identified. Identifying these factors and understanding their dynamics can assist in developing strategies which will help in overcoming these challenges. The study utilised a multiple case study approach. Choosing businesses situated in the same geographical area ensured that certain external factors were held constant (for example, the socio-economic status of the surrounding community, distance from economic hubs, and crime levels), and therefore the use of multiple case studies allowed. Qualitative data was collected from eight small business owners using semi-structured interviews in order to obtain a detailed picture of each owner and their business, and to enable a detailed descriptive analysis of each participant. The data was analysed using Tesch’s data reduction method. The research revealed several common challenges, including inadequate government support, lack of appropriate business management skills, poor infrastructure, and insufficient access to financial resources. Based on the findings it was concluded that conducive operating conditions, particularly in relation to economic and social factors, are crucial for the success of SMMEs in economically deprived areas.